'Building a new public idea about language'?: Multilingualism and language learning in the post-Brexit UK. Issue 2 (15th March 2022) - Copland, Fiona; McPake, Joanna
ABSTRACT: In 2003, Mary Louise Pratt published a hugely influential paper in Profession where she took to task misconceptions about multilingualism and language learning apparent in the USA in the wake of 9/11 and consequent counter-terrorism measures. She argued that a new public idea about language was necessary in order to ensure unity and security. This article argues that in the aftermath of Brexit, the UK also needs to develop a new public idea about language to ensure a future that is prosperous, socially, culturally and economically. To do so, it first challenges a number of prevalent myths about language learning and multilingualism in the UK through a review of scholarship, media articles and reports which focus on languages and multilingualism since 2013. It then suggests that interest in the Anglosphere has meant that the value of English is now artificially inflated and that the value of other languages is underplayed. We argue that this turn to the Anglosphere and to (English) monolingualism should be challenged through proposing a new public idea about language for post-Brexit UK.